PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS V SEKOLAH DASAR PEKANBARU - Syaharani, Dafinna; Alpusari, Mahmud; Astuti Mulyani, Eva; Dwi Anggriani, Mitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ science process skills in science education at the elementary school level, which is still dominated by teacher-centered instruction. The purpose of this study was to determine the effect of the Discovery Learning model on the science process skills of fifth-grade students at an elementary school in Pekanbaru. This study employs a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The research subjects were 54 fifth-grade students at SD Negeri 105 Pekanbaru, comprising Class VA as the experimental group and Class VE as the control group. Data collection techniques included KPS test questions, observation, and documentation. The data were analyzed using descriptive and inferential statistics, including tests of normality, tests of homogeneity, paired-sample t-tests, N-Gain tests, and independent-sample t-tests. The results of the study showed that the mean pretest score for the experimental class was 41.30, increasing to 78.15 on the posttest, while the control class’s score increased from 35.37 to 44.26. The results of the hypothesis test showed a significance value of 0.000 < 0.05, indicating a significant effect of the Discovery Learning model on students’ science process skills. Furthermore, the N-Gain test results for the experimental class were 0.64, categorized as moderate, while those for the control class were 0.12, categorized as low. Thus, it can be concluded that the Discovery Learning model has a significant effect on improving the science process skills of fifth-grade students at SD Negeri 105 Pekanbaru.